Students and Clinical Agency Staff Mutually Benefit from Collaboration - Philipps, Rachel; Coughlin, Teresa (My University, 2011)
In this study clinical agency staff were assisted by undergraduate nursing students in overcoming the barriers that prevent them from utilizing research in their practice. Undergraduate students assisted agency staff in finding research while simultaneously learning how to obtain important and relevant research.
Color poster with text and photographs.
Keywords: Team nursing; Community Health Partnership (Eau Claire, Wis.); Nursing--Research--Evaluation; Nursing--Practice; Posters